Are Environmental Factors for Atopic Eczema in ISAAC Phase Three due to Reverse Causation? - Rutter, Charlotte E (2019)
Some previously described environmental associations for atopic eczema may be due to reverse causation. We explored the role of reverse causation by comparing individual- and school-level results for multiple atopic eczema risk factors. The International Study of Asthma and Allergies in Childhood (i.e, ISAAC) Phase Three surveyed children in schools (the sampling unit) regarding atopic eczema symptoms and potential risk factors. We assessed the effect of these risk factors on atopic eczema symptoms using mixed-effect logistic regression models, first with individual-level exposure data and second with school-level exposure prevalence. Overall, 546,348 children from 53 countries were included. At ages 6–7 years, the strongest individual-level associations were with current paracetamol use (odds ratio [OR] = 1.45, 95% confidence interval [CI] = 1.37–1.54), which persisted at school-level (OR = 1.55, 95% CI = 1.10–2.21), early-life antibiotics (OR = 1.41, 95% CI = 1.34–1.48), and early-life paracetamol use (OR = 1.28, 95% CI = 1.21–1.36), with the former persisting at the school level, whereas the latter was no longer observed (OR = 1.35, 95% CI = 1.00–1.82 and OR = 0.94, 95% CI = 0.69–1.28, respectively). At ages 13–14 years, the strongest associations at the individual level were with current paracetamol use (OR = 1.57, 95% CI = 1.51–1.63) and open-fire cooking (OR = 1.46, 95% CI = 1.33–1.62); both were stronger at the school level (OR = 2.57, 95% CI = 1.84–3.59 and OR = 2.38, 95% CI = 1.52–3.73, respectively). Association with exposure to heavy traffic (OR = 1.31, 95% CI = 1.27–1.36) also persisted at the school level (OR = 1.40, 95% CI = 1.07–1.82). Most individual- and school-level effects were consistent, tending to exclude reverse causation.